Strengthening the Concept of Satirical Language through Analyzing the Connotations in the Lyrics of the Song "Cincin" by Hindia - Dewi Kusumaningsih; Meilisa Nurhana; Sukarno; Eka Susylowati (Journal of linguistics, culture and communication, 2024)
Innuendo serves to enhance the understanding of the meanings of a song. Hence, this article aims to provide insights into strengthening the concept of satirical language within a song. The research employed a qualitative descriptive approach. The focus was explicitly on the song "Cincin" by Hindia, sourced from a YouTube video. The data consisted of words and sentences found in the song lyrics, which were subsequently transcribed from the video and converted into narrative forms. The analysis in this study was descriptive, outlining patterns of word selection and sentences conveying satirical meaning in the song lyrics. The results demonstrated various forms of satirical language and different degrees of satirical meaning, illustrating that songwriters carefully considered concepts to reinforce satirical language in the compositions, encompassing irony, sarcasm, and cynicism. Correspondingly, the gradation of the satirical sense within the song included implicit and explicit meanings. The primary objective of this research was to delineate various forms of satirical language and the gradations of meanings within the lyrics of the song "Cincin" by Hindia. This case study is essential for providing song listeners with a comprehension of the use of satirical language by songwriters to convey social criticism. Hence, this research yielded findings regarding the selection of various forms of satirical language containing appropriate meanings and concepts, refining the accuracy and development.